2015
DOI: 10.3109/08037051.2014.997102
|View full text |Cite
|
Sign up to set email alerts
|

Deep breathing: A simple test for white coat effect detection in primary care

Abstract: DBT is a reliable, inexpensive and fast test for the detection of WCH in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A deep breathing test might be used as another strategy to target or minimize the usage of outside BP monitoring. In a clinical study, patients are unlikely to have WCHTN identified using ABPM if their systolic BP fell by 15% or less following 30 seconds of deep breathing [ 141 ].…”
Section: Reviewmentioning
confidence: 99%
“…A deep breathing test might be used as another strategy to target or minimize the usage of outside BP monitoring. In a clinical study, patients are unlikely to have WCHTN identified using ABPM if their systolic BP fell by 15% or less following 30 seconds of deep breathing [ 141 ].…”
Section: Reviewmentioning
confidence: 99%
“…In the Federico et al study, the DBT resulted in a statistically significant difference in mean SBP drop of 17.8 and 10.9 mmHg ( p < 0.001) among patients with or without white-coat effect respectively [29]. In the Marion et al study, a 15% drop in SBP was found to be corresponded to a 96% specificity (95% CI 79.0–100.0) and 94% positive predictive value (95% CI 72.0–100.0) in the diagnosis of white-coat hypertension [30]. The Jose et al study evaluated the diagnostic accuracy of DBT on identifying white-coat hypertension.…”
Section: Introductionmentioning
confidence: 99%